Mechanism of complement inactivation by glycoprotein C of herpes simplex virus. - Ioanna Kostavasili; Arvind Sahu; Harvey M. Friedman; Roselyn J. Eisenberg; Gary H. Cohen; John D. Lambris (1997)
Glycoprotein C (gC) of both herpes simplex virus type 1 (HSV-1) and HSV-2 interacts with complement C3b and protects the virus from complement-mediated neutralization. To study the mechanism by which gC modulates complement activation, we expressed both gC-1 and gC-2 in a baculovirus expression system. Baculovirus recombinants containing gC genes spanning the entire gC-1 sequence (gC-1-TMR) or only the extracellular domain(s) of gC-1, gC-2, or a deletion mutant of gC-1 lacking residues 33 through 123 were expressed in sf9 insect cells. Binding of the expressed proteins to human C3 and C3 fragments was assessed by direct and competition ELISA. All four expressed proteins bound to C3, C3b, and C3c but not to C3d, suggesting 1) that the binding sites for these proteins are located in the C3c region of C3; and 2) that gC, in contrast to other C3-binding proteins, interacts with native C3. We have also examined the interaction of native C3 with gC-1 expressed on the HSV-1-infected cells. Analogous to recombinant proteins, gC-1 expressed on the infected cells also bound to native C3. The ability of baculovirus-expressed gCs to inhibit the interaction of C3b with its ligands was also analyzed. We found that gC-1, but not gC-2, inhibited the binding of C5 and properdin to C3b and also inhibited the alternative pathway-mediated lysis of rabbit erythrocytes. Inhibition of alternative pathway-mediated lysis and properdin binding to C3b, but not of C5 binding to C3b, required the transmembrane segment of the gC-1. The specificity of gC interactions was examined by studying the interaction of gC with C3 from various species. In contrast to properdin, both gCs bound to cobra C3; this finding suggests that gC-1 and properdin bind to different sites on C3b. Further analyses suggested that gC-1 sterically hindered access of C5 and properdin to C3b.